On the Solutions of Linear Fractional Differential Equations of Order \(2q\), Including Small Delay Where \( 0< q - Demir, Ali; Karapınar, Kübra; Erman, Sertaç (Communications in Mathematics and Applications, 2020)
The main goal of this study is to find the solutions of linear fractional differential equations of order \(2q\), including small delay, where \(0
Keywords: Fractional differential; Small delay